Genetic and clinical characteristics of patients with Shwachman Diamond syndrome with special consideration of treatment with granulocyte-colony stimulating factor - Sabine Mellor-Heineke; Julia Skokowa; Natali Gerschmann; Ekaterina Deordieva; Ivan Tesakov; Sally Kinsey; Maja Klaudel-Dreszler; Piero Farruggia; Martina Sukova; Mikael Sundin; Yasmine El Chazli; Tania N. Masmas; et al. (Haematologica)
Not available.